Claudia in the storm : a Hurricane Katrina survival story - McConduit, Denise Walter; Ficorilli, Francesca (North Mankato, Minnesota : Stone Arch Books, 2024)
During the evacuation after Hurricane Katrina, twelve-year-old Claudia and her younger sister are separated from the rest of their family, and now it is up to Claudia to protect and comfort her sister through the tragedy.
4.1
3-6
710L
Keywords: Survival -- Juvenile fiction; Sisters -- Juvenile fiction; Hurricane Katrina, 2005 -- Juvenile fiction; African Americans -- Juvenile fiction; New Orleans (La.) -- Juvenile fiction; Survival -- Fiction; Sisters -- Fiction; Hurricane Katrina, 2005 -- Fiction; African Americans -- Fiction; New Orleans (La.) -- Fiction; Historical fiction